2007
DOI: 10.1128/jcm.02144-06
|View full text |Cite
|
Sign up to set email alerts
|

PCR Detection of Entamoeba histolytica , Entamoeba dispar , and Entamoeba moshkovskii in Stool Samples from Sydney, Australia

Abstract: This study investigated the presence of Entamoeba histolytica, Entamoeba dispar, and Entamoeba moshkovskii in stool samples from a patient population in Sydney, Australia. Stool samples were tested by microscopy and PCR. Five patients were found with E. histolytica infections, while E. dispar and E. moshkovskii were observed in 63 (70.8%) and 55 (61.8%) patients, respectively, by PCR. This is the first study in Australia using molecular techniques to determine the presence of E. histolytica, E. dispar, and E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
100
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 14 publications
11
100
1
1
Order By: Relevance
“…Microscopic examination of permanently fi xed, stained fecal smears was positive for E. histolytica/dispar/moshkovskii complex. Diagnosis of E. histolytica was confi rmed by PCR targeting the small subunit ribosomal DNA as described (8). Results of serologic examination of these patients were positive; all titers were >256 according to indirect hemagglutination antibody assay, which confi rmed invasive disease.…”
Section: The Casesmentioning
confidence: 99%
“…Microscopic examination of permanently fi xed, stained fecal smears was positive for E. histolytica/dispar/moshkovskii complex. Diagnosis of E. histolytica was confi rmed by PCR targeting the small subunit ribosomal DNA as described (8). Results of serologic examination of these patients were positive; all titers were >256 according to indirect hemagglutination antibody assay, which confi rmed invasive disease.…”
Section: The Casesmentioning
confidence: 99%
“…1 This procedure is cheap and simple, but it has several limitations, such as being incapable of distinguishing between the cysts and trophozoites of the disease-causing species Entamoeba histolytica , the nonpathogenic Entamoeba dispar , and the free-living amoeba Entamoeba moshkovskii . A high prevalence and association of E. moshkovskii with E. histolytica and E. dispar has been reported in young children from Bangladesh 2,3 and E. moshkovskii was recently detected in patients between 31 and 50 years of age presenting with gastrointestinal symptoms in Australia 4 ; therefore, humans may be a true host for this amoeba. This observation has made the differentiation of the three species in clinical samples of great importance, both for diagnosis and for epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%
“…6,8 However, most studies that have investigated the prevalence of E. histolytica and E. dispar have not considered the possible presence of E. moshkovskii , due partly to a lack of tools to detect E. moshkovskii other than cultivation, 12 which is laborintensive, not always successful, and problematic in the case of mixed infections. Recently, conventional PCR assays for E. moshkovskii in clinical diagnosis of amoebiasis have been performed 3,4,13,14 but most of the protocols reported so far require further processing of the amplicon, which is timeconsuming and prone to false-positive results caused by possible cross-contamination.…”
Section: Introductionmentioning
confidence: 99%
“…15 A study from Sydney showed high rates of intestinal parasites in MSM, with 52.2% of stool specimens positive for protozoa, compared with 13% from non-MSM, of which E. histolytica had a prevalence rate of 0.24% in the MSM group. 16 Another report of five cases of invasive amebiasis in MSM from Sydney further documents its existence in this at risk group.…”
mentioning
confidence: 99%
“…4 Improved methods of detection, with greater sensitivity and specificity include antigen and antibody detection and polymerase chain reaction. 15,18 Serum antibody detection is most useful in patients with extra-intestinal disease and is able to detect antibodies specific for E. histolytica. Sensitivity of these tests is ~95% for patients with amoebic abscesses, 70-85% for patients with active amoebic colitis, and 10-20% for asymptomatic people passing cysts, with specificity of 95% generally reported, 19,20 and E. histolytica -specific antibodies persisting for many years after exposure.…”
mentioning
confidence: 99%